Security and accountability for sharing the data stored in the cloud‏ - Mohammed, Mostafa Abdulghafoor; Salih, Zeyad Hussein; Tapus, Nicolae; Hasan, Raed Abdulkareem (IEEE, 2016)
Important for cloud services the cloud computing share throw multiple clients , and it is more important to allocate resources for cloud service provider , cloud computing is an infrastructure that provides on demand network services , in relation , the most important feature of the cloud services is that user’s data are hosted in remote . While taking benefit of this new emerging technology, users’ fear of losing command of their own data, is becoming a noteworthy hurdle to the extensive implementation of cloud services. Cloud service provider module is to process data owner request for storing data files and application and provides cloud users log details to data owner for audit purpose, to address this problem framework based on information accountability to keep track and trial of the authentic handling of the users’ data in the cloud. The system proposed that the Data can be fully tracked by the owner and follow up the service agreements by depending on many items which access, usage control and management.